Analisa Kekuatan Tahanan Lateral Pada Sistem Komposit LVL Kayu Sengon dan Beton Pracetak - Tantisaputri, Intan Archita; Awaludin, Ali; Siswosukarto, Suprapto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
LVL Sengon and concrete can be used to form a composite structure of the floor system. Connections between LVL Sengon and concrete on this composite floor system are the weakest part so that a majority of structural damages are concentrated at these joints. This study discusses the lateral resistance of lag screw joints in a composite system of LVL Sengon and precast concrete. The lateral joint resistance was evaluated through quasi-static loading upon double shear test specimens having two screws at every single shear. Variation of the specimens includes precast concrete compressive strength of 20.71 MPa and 25.29 MPa, screw diameter of 6 mm length 101.6 mm and 8 mm length 101.6 mm and 127 mm, and angle of lag screw axis against the wood fiber of 60° and 90°. The result shows that lateral resistance of the test is greater than that of EYM, SNI, and EC5 predictions. Joint failure in this experiment is due to failure in wood fiber along with the occurrence of one up to two plastic hinges in the screw.